PIM-Related Kinases Selectively Regulate Olfactory Sensations in Caenorhabditis elegans - Karunambigai S. Kalichamy; Kaisa Ikkala; Jonna Pörsti; Niina M. Santio; Joel Tuomaala; Sweta Jha; Carina I. Holmberg; and Päivi J. Koskinen (Society for Neuroscience, 2022)
The mammalian PIM family of serine/threonine kinases regulate several cellular functions, such as cell survival and motility. Because PIM expression is observed in sensory organs, such as olfactory epithelium, we now wanted to explore the physiological roles of PIM kinases there. As our model organism, we used the Caenorhabditis elegans nematodes, which express two PIM-related kinases, PRK-1 and PRK-2. We demonstrated PRKs to be true PIM orthologs with similar substrate specificity as well as sensitivity to PIM-inhibitory compounds. When we analyzed the effects of pan-PIM inhibitors on C. elegans sensory functions, we observed that PRK activity is selectively required to support olfactory sensations to volatile repellents and attractants sensed by AWB and AWCON neurons, respectively, but is dispensable for gustatory sensations. Analyses of prk-deficient mutant strains confirmed these findings and suggested that PRK-1, but not PRK-2 is responsible for the observed effects on olfaction. This regulatory role of PRK-1 is further supported by its observed expression in the head and tail neurons, including AWB and AWC neurons. Based on the evolutionary conservation of PIM-related kinases, our data may have implications in regulation of also mammalian olfaction.